2017
DOI: 10.1002/jcb.26105
|View full text |Cite
|
Sign up to set email alerts
|

Picroside II Inhibits RANKL‐Mediated Osteoclastogenesis by Attenuating the NF‐κB and MAPKs Signaling Pathway In Vitro and Prevents Bone Loss in Lipopolysaccharide Treatment Mice

Abstract: Picroside II, one of the major components isolated from the seed of natural plant picrorhiza, is widely used in traditional Chinese medicine. The present study was performed to define effects of picroside II on nuclear factor-kappaB ligand (RANKL)-stimulated osteoclast differentiation in vitro and on lipopolysaccharide (LPS)-induced bone loss in vivo. The bone marrow cells (BMMs) were harvested and induced with RANKL followed by treatment with picroside II at several doses, and the differentiation of osteoclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Cytotoxicity of PI on BMMs were performed as our previously described [17, 18]. Briefly, BMMs were seeded at a density of 3.5×10 3 cells per well in 96-well plates with various concentrations of PI and incubated for 3 d in the presence of RANKL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity of PI on BMMs were performed as our previously described [17, 18]. Briefly, BMMs were seeded at a density of 3.5×10 3 cells per well in 96-well plates with various concentrations of PI and incubated for 3 d in the presence of RANKL.…”
Section: Methodsmentioning
confidence: 99%
“…Mature OCs function evaluated by bone absorption assay [19] and F-actin ring immunofluorescence as previously described respectively [17]. Briefly, cells were treated with 50 ng/ml RANKL on 6-well plates pre-coated with collagen for 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the lack of effort by most of the large pharmaceutical companies, natural product research has still been active during the past decade . Institutions mainly from China, Korea, India, Japan and United States keep engaging in the work of natural products study, for re‐establish natural products as a major source for potential drug discovery . Given that only limited biological properties or functional activities have been worked out for each natural product, there still has a “long way to go” for fully identifying the biological activities of natural products .…”
Section: Discussionmentioning
confidence: 99%
“…Others reported that (a) picroside II had a certain bone protection effect and could be used as an osteoclast blocker against bone resorption (Yang, Gao, & Wang, ); (b) oral administration of RP had the antagonistic effect on gastric ulcer induced by hydrochloric acid‐ethanol in rats (Anandan, Rekha, & Saravanan, ); (c) the water extract of RP had the inhibitory effect on some superficial fungi at 5% concentration (Wang, Yang, & Yang, ); and (d) RP could also reduce the damage of kidney caused by metal cadmium poisoning (Wang et al, 2017). In addition, RP can also improve and prolong the ovarian function, treat and alleviate menopausal symptoms, improve depression, and so on (Zhang et al, ).…”
Section: Pharmacologymentioning
confidence: 99%